Optimizing cellulose acetate microbead formation through premixed membrane emulsification: Unraveling critical parameters - Jisoo Lee; Kie Yong Cho; Eun Hyup Kim; Hoik Lee (Carbohydrate Polymer Technologies and Applications)
This study explores the fabrication of cellulose acetate microbeads using the premix membrane emulsification technique and their subsequent conversion to cellulose microbeads through deacetylation, emphasizing the need for environmentally friendly alternatives to conventional synthetic microbeads. By systematically investigating critical processing parameters such as oil-to-water phase ratio, cellulose acetate concentration, dispersion solvent, drying temperature, and flux rate, we optimized the conditions for producing uniform and well-dispersed microbeads. The optimal oil-to-water phase ratio was identified at 6:1, with higher concentrations of cellulose acetate yielding better dispersion and reduced bead size. The flux rate significantly influenced the morphology of the microbeads, with lower rates favoring spherical shapes. Non-polar solvents like hexane were found to enhance bead dispersion, whereas the drying temperature showed no significant impact. The successful transformation from cellulose acetate to cellulose microbeads was confirmed by FT-IR spectroscopy, demonstrating the removal of acetyl groups and indicating complete deacetylation. Our findings provide valuable insights into the production of cellulose-based microbeads, offering a sustainable alternative for various industrial and environmental applications.